Religion, Ethnicity and Social Change - Fawcett, L. author. aut Link
XVI, 220 p.
Keywords: In Religion, Ethnicity and Social Change the author argues that the recent focus on religious fundamentalism in ethnic conflict has obscured the ambiguous role of 'mainstream' Western religion. The book examines the relationship between the religious and secular spheres at a time of rapid transition in South Africa and Northern Ireland.